2014
DOI: 10.1080/19393210.2014.888783
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in vegetables and respective soils irrigated by canal, municipal waste and tube well waters

Abstract: Heavy metal contamination in the food chain is of serious concern due to the potential risks involved. The results of this study revealed the presence of maximum concentration of heavy metals in the canal followed by sewerage and tube well water. Similarly, the vegetables and respective soils irrigated with canal water were found to have higher heavy metal contamination followed by sewerage- and tube-well-watered samples. However, the heavy metal content of vegetables under study was below the limits as set by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 23 publications
3
25
1
Order By: Relevance
“…The results indicated that sewage wastewater use in irrigating these vegetables caused a significant increase in Pbcontent in their edible portions. These results are in an agreement with those of Rattan et al (2005) and Ismail et al(2014). Also, Eissa.…”
Section: Lead (Pb)supporting
confidence: 82%
See 3 more Smart Citations
“…The results indicated that sewage wastewater use in irrigating these vegetables caused a significant increase in Pbcontent in their edible portions. These results are in an agreement with those of Rattan et al (2005) and Ismail et al(2014). Also, Eissa.…”
Section: Lead (Pb)supporting
confidence: 82%
“…Thus, levels of Ni in the edible parts of these plants were higher than its permissible limit level. These results are in the same line with those of Rattan et al (2005) and Ismail et al (2014). The prolonged application of treated and untreated wastewatersresults in significant buildup of heavy metals in the soils (Khan et al, 2008;Ullah et al, 2011;Gosh et al, 2012) and grown vegetables and cereals which are subsequently transfer to the food chain causing potential health risk to consumers (Sharma et al, 2006;Singh et al, 2010;Gupta et al, 2011).…”
Section: Nickel (Ni)supporting
confidence: 78%
See 2 more Smart Citations
“…Nickel (Ni) is a trace mineral element required for the normal growth and maintenance of human body but the excessive doses of Ni may result in carcinogenicity, neurotoxicity, reproductive disorders and may also result in oxidative stress (Ismail et al, 2014;. Significant differences were observed in the Ni concentration of oil samples collected from different zones of Multan city.…”
Section: Minerals and Heavy Metals In Oilmentioning
confidence: 87%